Lycian Way and Recreation Activities Within the Scope of Alternative Tourism - Kurar, ihsan; Kavacık, Mustafa (Journal of History Culture and Art Research, 2023)
The Lycian Way, with a length of 540 km, is the longest walking path detected in Turkey. Considering historically, it was formed by combining the ancient roads connecting the cities of the Lycian League. The purpose of this study is to reveal the alternative tourism potential of the Lycian Way in the framework of SWOT analysis. The alternative tourism potential of the Lycian Way has been disclosed via a case study, which is one of the qualitative research methods. The sample of the research consists of twelve sector representatives. Semi-structured interview forms were used in the research. The data obtained from the face-to-face interviews were analyzed with the "Content Analysis Method" in the NVivo 12 qualitative data editing program. Participant opinions were collected in four categories and 24 codes. The reliability coefficient of the codings was determined as 0.84. As a result of the internal environment analysis; the historical-cultural areas, natural heritage and rich vegetation of the region were determined as strengths; route uncertainty, labor and accommodation problem were determined as weaknesses. In the external environment analysis, inert buildings that can be used for touristic purposes due to migration and geographical inventory are seen as opportunities due to its position as an alternative tourism center. Unconsciousness, trust and seasonal effects are considered as threats.